2011
DOI: 10.1111/j.1472-765x.2011.03024.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Laribacter hongkongensis from Little Egrets (Egretta garzetta) in Hangzhou, China

Abstract: Aims:  Laribacter hongkongensis is well adapted to diverse freshwater environments and is associated with human community‐acquired gastroenteritis and traveller’s diarrhoea. The study intended to investigate whether L. hongkongensis could be detected in Little Egrets (Egretta garzetta, a widespread aquatic bird) in Hangzhou, China. Methods and Results:  A total of 176 faecal specimens from three habitats in Hangzhou were obtained for this study. L. hongkongensis was isolated from 12 (6·8%) specimens. Identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…L. hongkongensis has been found in up to 60% of the intestines of commonly consumed freshwater fish of the carp family [7,8]. It has also been isolated from drinking water reservoirs and Chinese tiger frogs in Hong Kong and little egrets in Hangzhou [9-11]. Pulsed-field gel electrophoresis and multilocus sequence typing showed that the fish and patient isolates fell into separate clusters, suggesting that some clones could be more virulent or adapted to human [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…L. hongkongensis has been found in up to 60% of the intestines of commonly consumed freshwater fish of the carp family [7,8]. It has also been isolated from drinking water reservoirs and Chinese tiger frogs in Hong Kong and little egrets in Hangzhou [9-11]. Pulsed-field gel electrophoresis and multilocus sequence typing showed that the fish and patient isolates fell into separate clusters, suggesting that some clones could be more virulent or adapted to human [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…L hongkongensis has been found in up to 60% of the intestines of commonly consumed freshwater fish of the carp family 1. It has also been isolated from drinking water reservoirs and Chinese tiger frogs in Hong Kong and little egrets in Hangzhou 1 9 10. Pulsed field gel electrophoresis and multilocus sequence typing showed that the fish and patient isolates fell into separate clusters, suggesting that some clones could be more virulent or adapted to humans 1 11.…”
Section: Introductionmentioning
confidence: 99%
“…In all previous cases of human L. hongkongensis infection and in reports of the detection of this species in animal specimens, the strains were identified using a combination of phenotypic tests and 16S rRNA gene sequencing. 2,7,8,9,10,11,19,20,21 In recent years, MALDI–TOF MS has emerged as a revolutionary technique for rapid bacterial identification at a low cost. Using an expanded Bruker database with L. hongkongensis reference strains, we recently found that all 240 L. hongkongensis isolates could be correctly identified using MALDI–TOF MS, demonstrating the importance of expanding the MALDI–TOF MS database with bacteria endemic to different localities.…”
Section: Discussionmentioning
confidence: 99%
“…2,8 This species has also been isolated from drinking water reservoirs, Chinese tiger frogs and little egrets. 9,10,11 Pulsed-field gel electrophoresis and multilocus sequence typing (MLST) demonstrated that the fish and patient isolates fall into separate clusters, suggesting that some clones could be more virulent or adapted to humans. 8,12 The complete genome of L. hongkongensis was recently sequenced, and this bacterium's mechanism of acid resistance was characterized.…”
Section: Introductionmentioning
confidence: 99%